Uncorrelated Phase Noise Analysis for Millimeter-Wave Radiometer Imager Frequency Synthesizer - Jin Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, a nontrivial uncorrelated phase noise analysis is proposed for frequency synthesizer of a passive millimeter-wave Synthetic Aperture Interferometric Radiometer (SAIR) imager named BHU-2D-U designed for concealed weapon detections on human bodies with high imaging rates. This synthesizer provides local oscillators both for millimeter-wave front-ends and intermediate frequency IQ demodulators for the receivers. The influence of synthesizer uncorrelated phase noise in different offset frequency ranges on the visibility phase errors have been systematically investigated with phase noise mismatch requirements drawn. Integrated RMS phase error has been applied to establish uncorrelated phase noise requirements for visibility error control. Measurement results have proved that uncorrelated phase noise does exist among synthesizer output pairs, and the previously defined requirements are achieved with imaging results proposed. In conclusion, the uncorrelated phase noise effects on SAIR visibility errors have been concretized to phase noise design requirements, which have been realized by synthesizer design. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3844